AKUNTABILITAS PENGGUNAAN DANA DESA KABUPATEN KEPULAUAN TALAUD DI DESA KARATUNG KECAMATAN NANUSA - PANGALO, BRAMSES; TAMPI, GUSTAAF BUDDY; LONDA, VERY (Sam Ratulangi University, 2019)
The purpose of this study was to determine the accountability for the use of Village Funds in theSouth Karatung Village, Manusa District, Talaud Islands Regency. This research uses a descriptive qualitativeapproach. Accountability for the use of Village Funds can be seen from three dimensions ofpublic accountability, namely financial accountability, benefit/effectiveness accountability, andprocedural accountability. The research informants were the village head, village secretary, villagetreasurer, BPD chair, LPMD chair, and several figures and residents of South Karatung Village. Datacollection uses interview guidelines, while the analysis technique used is an interactive model analysisfrom Miles and Hubernann. The results of the study show: (1) Financial Accountability is good enough,that is the received Village Funds are announced or informed transparently to the general public; its useplanning involves the BPD and LPM, as well as elements of community representatives, and the results ofthe implementation are accounted for in a transparent manner by the authorities and informed to thewider community. (2) Accountability Benefits / Effectiveness is quite good, namely: the program isplanned/determined according to the needs of the village community; the benefits can be felt by thecommunity in terms of improving public services and in improving the standard of living and welfare ofthe community. (3) Procedural accountability is good enough, i.e. program planning is determinedthrough village deliberations involving all relevant elements in the community; program/activityimplementation procedures in accordance with the implementation instructions and technicalmanagement guidelines; and reporting and accountability mechanisms are carried out properly inaccordance with village financial management guidelines.Keywords: Accountability, Village Funds.